Effects of Distribution Requirements Planning on Fill Rate and Average Inventory - Mattsson,Ellen; Sjölin,Anton (2025)
Background: The Case Company is in the process of implementing a new inventory control policy for their spare parts distribution, from a single-echelon inventory control policy, specifically what is called an (R, Q) policy, to a multiechelon inventory control policy called Distribution Requirements Planning. It is of interest to see how this new policy will perform, and the effect this change has on the average inventory and fill rate were chosen as the research focus. Purpose: The purpose of this thesis is to investigate the impact of using a multiechelon Distribution Requirements Planning (DRP)-policy for inventory control, instead of a sequence of uncoordinated single-echelon (R, Q)-policies in terms of average inventory and fill rate, using discrete event simulation. Methodology: For the overall research methodology, the thesis follows an explorative research design for the first part of the thesis, which includes mainly the literature review but also interviews. In the second part of the thesis, the research is based on discrete-event simulation. Conclusion: In conclusion, the study found it to only be a small difference in performance between the DRP and (R, Q) policies in terms of average inventory and fill rate. Similar overall performance is still promising for the Case Company, suggesting that the DRP policy can replace the current inventory control system without decreasing performance while offering additional benefits such as improved information visibility. It is of interest to the Case Company to investigate other methods of determining safety stock for the DRP policy, to see if that could improve the performance of the policy.
Keywords: Distribution Requirements Planning; (R; Q) policy; Fill rate; Average inventory.